Self-evaluation in Graduate Education: a replicable model from the experience of a municipal public institution (Práxis Educativa, 2025)
Self-evaluation practices play a central role in the management and improvement of Graduate Education Programs. In Brazil, however, many still take on a merely descriptive character, with limited connection to decision-making and social impact. This study critically analyzes the self-evaluation of the Professional Graduate Program in Education (2021-2024) at a municipal public university in São Paulo, aiming to transform it into a strategic, evidence-based routine. The methodology combined documentary analysis, a survey with alumni, interviews, and Master’s theses (supported by Natural Language Processing), along with a SWOT synthesis operationalized through the 5W2H method. Despite the high quality of coursework and faculty performance, challenges remain in infrastructure and feedback processes, as the coherence across the theses contrasts with the need to strengthen knowledge transfer to school networks. Nevertheless, the approach produced verifiable action plans and reinforced governance. For 2025-2028, the proposal is to establish a public, cumulative self-evaluation regime with transfer metrics, ongoing internationalization, and specific goals for equity and infrastructure.Keywords: Teacher education. Institutional evaluation. Social impact. 2030 Agenda.